UJI DAYA HAMBAT PERTUMBUHAN JAMUR PATOGEN DERMATOFITA SPESIES Trycopyton mentagrophytes dan Trycophyton rubrum DARI EKSTRAK ETANOL 96% BUNGA KECOMBRANG - Octaviana Dyah Oentari; Andri Tri Cahyono; Usman Setiawan; Barolym Tri Pamungkas; Sinta Wisma Sari (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2021)
Dermatophytes are a skin disease caused by mycosis or fungi found on the skin. This fungus has the potential to grow in tropical environments and high humidity. Indonesia is a part of the country that has a tropical environment and high humidity, so it has the potential for disease and skin infections caused by pathogenic fungi. Trycophyton mentagrophytes and Trycophyton rubrum are pathogenic fungi that can cause dermatophytes. Long-term use of synthetic drugs causes resistance to the fungus and also irritation of the skin organs, so traditional treatments need to be reaffirmed which have been used for generations. One traditional or herbal-based treatment is to use kecombrang flowers which are extracted through 96% ethanol. This is because the phytochemical content of the kecombrang plant has been proven to have various pharmacological activities, especially in inhibiting the growth of pathogenic fungi. This research aims to provide the latest scientific information regarding the growth inhibitory power of pathogenic fungi from 96% ethanol extract of kecombrang flower plant organs in inhibiting the growth of the two test pathogenic fungi. This resistance test was carried out using the well method. The results of this research have proven that the ethanol extract of kecombrang flowers correlates positively and comprehensively as an antidermatophyte and it can be concluded that a concentration of 15% is the optimal treatment as an antidermatophyte